How inflation affects macroeconomic performance: An agent-based computational investigation - Quamrul Ashraf; Boris Gershman; Peter Howitt (Brown University, Department of Economics, 2012)
We use an agent-based computational approach to show how inflation can worsen macroeconomic performance by disrupting the mechanism of exchange in a decentralized market economy. We find that increasing the trend rate of inflation above 3 percent has a substantial deleterious effect, but lowering it below 3 percent has no significant macroeconomic consequences. Our finding remains qualitatively robust to changes in parameter values and to modifications to our model that partly address the Lucas critique. Finally, we contribute a novel explanation for why cross-country regressions may fail to detect a significant negative effect of trend in ation on output even when such an effect exists in reality.
Keywords: C63; E00; E31; E50; 330; agent-based computational model; inflation; price dispersion; firm turnover; Inflation; Makroökonomischer Einfluss; Gesamtwirtschaftliche Produktion; Neue klassische Makroökonomik